Involving patients in health technology funding decisions: stakeholder perspectives on processes used in Australia. (21st February 2015) - Lopes, Edilene; Street, Jackie; Carter, Drew; Merlin, Tracy
Abstract: Background: Governments use a variety of processes to incorporate public perspectives into policymaking, but few studies have evaluated these processes from participants' point of view. Objective: The objective of this study was twofold: to understand the perspectives of selected stakeholders with regard to involvement processes used by Australian Advisory Committees to engage the public and patients; and to identify barriers and facilitators to participation. Design: Twelve semi‐structured interviews were conducted with representatives of different stakeholder groups involved in health technology funding decisions in Australia. Data were collected and analysed using a theoretical framework created by Rowe and Frewer, but adapted to more fully acknowledge issues of power and influence. Results: Stakeholder groups disagreed as to what constitutes effective and inclusive patient involvement. Barriers reported by interviewees included poor communication, a lack of transparency, unworkable deadlines, and inadequate representativeness. Also described were problems associated with defining the task for patients and their advocates and with the timing of patient input in the decision‐making process. Interviewees suggested that patient participation could be improved by increasing the number of patient organizations engaged in processes and including those organizations at different stages of decision making, especially earlier. Conclusions: The different evaluations made by stakeholder groups appear to be underpinned by contrasting conceptions of public involvement and its value, in line with Graham Martin's work which distinguishes between 'technocratic' and 'democratic' public involvement. Understanding stakeholders' perspectives and the contrasting conceptions of public involvement could foster future agreement on which processes should be used to involve the public in decision making.